Shelf life evaluation of Laghu Sutashekhara Rasa – A preliminary assessment - Shweta, Mata (J Ayurveda Integr Med, 2020)
BACKGROUND: Laghu Sutashekhara Rasa (LSR) is a herbo mineral formulation containing Shuddha Gairika (Fe(2)O(3)) and Shunthi (Zingiber officinale Roxb.) with the levigation of Nagawalli Swarasa (fresh juice of Piper betel Linn.) prepared as per the reference of Rasatarangini Parishistha. This is an important formulation in Ayurveda therapeutics, but its shelf life is not evaluated till date. The Govt. of India Gazette specifies the shelf life of various Ayurvedic medicines. However, there is a need to revalidate the shelf life of individual formulations by following parameters prevalent in respective scenario. OBJECTIVES: To evaluate shelf life of Laghu Sutashekhara Rasa. MATERIALS AND METHODS: Laghu Sutashekhara Rasa was prepared in the Pharmacy, Gujarat Ayurved University, Jamnagar following classical guidelines. The samples were subjected to accelerated stability study maintaining temperature and humidity 40 ± 2 °C and 75 ± 5% respectively. Relevant analytical parameters were analyzed at an interval of 0, 1, 3 and 6 months to check the degradation levels in the formulation. RESULT: Product was free from microbial contamination and heavy metals were within the prescribed limits. There were insignificant changes in physico-chemical profiles at different intervals of analysis. On extrapolation of the observations, the shelf life of Rasayoga was found to be 2 years and 8 months. CONCLUSION: The shelf life of Laghu Sutashekhara Rasa was found to be less than the given standards in official gazettes of Govt. of India. This decreased shelf life may be because of the predominantly (approximately 70%) herbal component present in the formulation.